The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1093/heapol/czw135
|View full text |Cite
|
Sign up to set email alerts
|

The impact of health insurance on maternal health care utilization: evidence from Ghana, Indonesia and Rwanda

Abstract: While research has assessed the impact of health insurance on health care utilization, few studies have focused on the effects of health insurance on use of maternal health care. Analyzing nationally representative data from the Demographic and Health Surveys (DHS), this study estimates the impact of health insurance status on the use of maternal health services in three countries with relatively high levels of health insurance coverage—Ghana, Indonesia and Rwanda. The analysis uses propensity score matching t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
153
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(185 citation statements)
references
References 51 publications
28
153
1
3
Order By: Relevance
“…Conversely, 93% of the respondents indicated that they completed the four mandatory ANC attendances in the Wa West District while the remainder did not fulfil it. This compares with the findings made by Wang et al [28] that the majority of pregnant women reported at least one antenatal care visit in Ghana.…”
Section: Utilisation Of Maternal Health Servicessupporting
confidence: 71%
See 1 more Smart Citation
“…Conversely, 93% of the respondents indicated that they completed the four mandatory ANC attendances in the Wa West District while the remainder did not fulfil it. This compares with the findings made by Wang et al [28] that the majority of pregnant women reported at least one antenatal care visit in Ghana.…”
Section: Utilisation Of Maternal Health Servicessupporting
confidence: 71%
“…Still, studies that relate to access to maternal healthcare under Ghana's NHIS appear to ignore rural idiosyncrasies associated with access to maternal healthcare services. Using 2008 DHS data, Wang et al [28] examine the impact of NHIS coverage on access to maternal healthcare services in Ghana and came to the conclusion that majority of pregnant women reported at least one antenatal care visit and facility-based delivery. The study presented a national picture but fell short of a discussion of access to maternal healthcare services in rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…Also, individuals with insurance are more likely to be from high‐income groups, educated, and from urban areas. These selection factors complicate the comparison of the insured and uninsured women and could cause bias unless they are carefully controlled for (Gertler et al ., ; Bonfrer, Breebaart, & Van de Poel, ; Wang, Temsah, & Mallick, ). We conduct a propensity score matching (PSM) analysis to limit the bias due to confounding factors when estimating the treatment effect by comparing outcomes between the treatment (the insured) and the artificial control groups (the uninsured).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have found that access to and utilization of prenatal care increased substantially due to the expansion of insurance coverage (Currie & Gruber, 1996a, 1996bMensah, Oppong, & Schmidt, 2010;Wang, Temsah, & Mallick, 2017). Several studies have found that access to and utilization of prenatal care increased substantially due to the expansion of insurance coverage (Currie & Gruber, 1996a, 1996bMensah, Oppong, & Schmidt, 2010;Wang, Temsah, & Mallick, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…One of the recommended policies to increase access to health care is the expansion of insurance coverage. Several studies have found that access to and utilization of prenatal care increased substantially due to the expansion of insurance coverage (Currie & Gruber, 1996a, 1996bMensah, Oppong, & Schmidt, 2010;Wang, Temsah, & Mallick, 2017). Prior research has argued that policies that increase prenatal care are strongly correlated with infant health, and therefore, expansion of health insurance program is likely to improve infant health through the increased use of prenatal care (Currie & Gruber, 1996a, 1996bHanratty, 1996).…”
Section: Introductionmentioning
confidence: 99%